FINGER TAPPING AND COGNITION IN PARKINSON'S. Issue 11 (14th October 2015) - Cosgrove, Jeremy; Lacy, Stuart; Jamieson, Stuart; Smith, Stephen; Alty, Jane
Abstract : Objective: To investigate separable components of finger tapping (FT) of the thumb and index finger in Parkinson's (PD) with normal (PD-NC) and impaired cognition (PD-CI) and in healthy controls (HC). Methods: 58 PD and 29 HC performed FT for 30 seconds whilst attached to electromagnetic movement sensors sampling at 60 Hz. All subjects completed the Montreal Cognitive Assessment (MoCA); PD-NC defined as MoCA score ≥26, PD-CI as MoCA score <26. Results: PD and HC were age-matched. Mean disease duration of PD 6.2 years, Hoehn and Yahr stage 1.9. Mean MoCA score PD 23.1, HC 26.3 (P<0.001). PD had significantly (P<0.01) smaller mean velocity and amplitude of FT, greater decrement of speed and greater variability of rhythm (speed and amplitude coefficient of variation). Age, disease duration, motor score and levodopa dose were not significantly different between PD-CI (n=36) and PD-NC (n=22). PD-CI had significantly less rhythmic FT movements than PD-NC (P<0.01) but other parameters were similar. MoCA score was negatively correlated with rhythm in PD (P 0.017). Conclusion: As expected PD have slower, less rhythmic FT movements with greater decrement than HC. Those with PD-CI have significantly less rhythmic movement than those with PD-NC – this finding is currently being investigated.